EXCHANGE RATE STABILITY IN ASEAN COUNTRIES DURING THE COVID-19 PANDEMIC - Pragita Aci Adistya; Agus Sumanto; Dwi Wulandari (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to analyze the effect of macroeconomic variables on exchange rate stability in five developing countries in Southeast Asia that are members of the Association of Southeast Nations (ASEAN) geopolitical and economic organization to see the short-term and long-term relationships during the COVID-19 pandemic. The data used is secondary data, from International Financial Statistics (IFS) for the period January 2020 to June 2022 using the Vector Error Correction Model (VECM). The results show that in the long run the variables that have a positive influence on exchange rate stability are lending rates, exports and the money supply. While the variables that have a negative influence are deposit rates, imports and the current account. In the short term, variables that have a positive influence on exchange rate stability are deposit rates, imports and the current account. However, the variable lending rates, exports and the money supply have a negative effect